The Effect of Ratio of Lemongrass Bar Juice with Ginger Juice and Concentration of Palm Sugar Powder on the Quality of Lemongrass Fresh Drink Powder - Devi Marista Togatorop; Rona J. Nainggolan; Linda Masniary Limbong (Universitas Sumatera Utara, 2015)
This research was conducted to determine the effect of ratio of lemongrass bar juice with ginger juice and concentration of palm sugar powder on the quality of lemongrass fresh drink powder . This research was conducted using completely randomized design (CRD) with two factors i. e: ratio of lemongrass bar juice with ginger juice (S) : (95% : 5 ; 90% : 10% ; 85% : 20% ; 80% : 20%) and concentration of palm sugar powder (G) : (12%, 14%, 16%, 18%). The parameters analyzed were water content, ash content, total acid, total soluble solid, solubility, solubility speed, the score value of color and taste, and the hedonic value of flavor and taste. The results showed the ratio of lemongrass bar juice with ginger juice had highly significant effect on water content and hedonic value flavor. Concentration of palm sugar powder had highly significant effect on water content, ash content, total acid, total soluble solid, solubility, solubility speed, the hedonic value of taste, and the score value of color. The interaction between the two factors had significant effect on water content and ash content. Ratio of lemongrass bar juice with ginger juice of 80% : 20% and concentration of palm sugar powder of 18% produced the best quality of lemongrass fresh drink powder . Keywords : Fresh drink powder, ginger juice, lemongrass bar juice, palm sugar powder.